Design zegarków naręcznych produkowanych przez ZMP „Błonie” - Piechaczek, Oliwia (Człowiek i Społeczeństwo, 2017)
Oliwia Piechaczek, Design zegarków naręcznych produkowanych przez ZMP „Błonie” [The design of wristwatches produced by ZMP „Błonie”], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 115-126, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271. The article is dedicated to the Polish brand of watches „Błonie” popular in the sixties and the seventies. The first part is dedicated to the history of creation and the development of the manufacture, while the second part is characterized by the designs of the particular models and their elements, like the commercial names, the dials, the cases and the packages. „Błonie” watches, for many years, were the most commonly bought watches in Poland. Owing to their timeless design, well-preserved models enjoy great popularity even today. The brand was brought back a few years ago, introducing new models based on the older designs.